Electrochemical Reduction of CO2 to Organic Acids by a Pd-MWNTs Gas-Diffusion Electrode in Aqueous Medium - Guang Lu; Hui Wang; Zhaoyong Bian; Xin Liu (The Scientific World Journal)
Pd-multiwalled carbon nanotubes (Pd-MWNTs) catalysts for the conversion of CO2 to organic acids were prepared by the ethylene glycol reduction and fully characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), and cyclic voltammetry (CV) technologies. The amorphous Pd particles with an average size of 5.7 nm were highly dispersed on the surface of carbon nanotubes. Functional groups of the MWNTs played a key role in the palladium deposition. The results indicated that Pd-MWNTs could transform CO2 into organic acid with high catalytic activity and CO2 could take part in the reduction reaction directly. Additionally, the electrochemical reduction of CO2 was investigated by a diaphragm electrolysis device, using a Pd-MWNTs gas-diffusion electrode as a cathode and a Ti/RuO2 net as an anode. The main products in present system were formic acid and acetic acid identified by ion chromatograph. The selectivity of the products could be achieved by reaction conditions changing. The optimum faraday efficiencies of formic and acetic acids formed on the Pd-MWNTs gas-diffusion electrode at 4 V electrode voltages under 1 atm CO2 were 34.5% and 52.3%, respectively.